USE OF N-LIST IN HIGHER EDUCATION INSTITUTIONS - Jha, Binita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's research landscape, accessing comprehensive information often requires navigating through extensive physical libraries or purchasing bulky books, which can be time-consuming, costly, and exhausting for researchers. However, the advent of E-Sources has revolutionized this process by offering efficient access to necessary information at a reduced cost and effort. The N-List specifically facilitates research by providing electronic access to a wide array of resources such as research articles, journals, and books. This platform not only simplifies research but also enables users to read, store, and evaluate electronic information conveniently. It is crucial for researchers, students, and higher education institutions to leverage the benefits of N-List to enhance research efficiency and awareness.